Association Between Cardiovascular Autonomic Function and Temporomandibular Disorders - Kakko, Niklas; Suominen, Auli; Somero, Atte; Tulppo, Mikko; Lahti, Satu; Pohjola, Vesa; Ogawa, Mika; Sipilä, Kirsi (Wiley, 2025)
Background: Studies have shown that elevated stress levels associate with TMD-related pain, which suggests that alterations in autonomic tone may contribute to this pain condition.
Objective: The aim of the study was to evaluate the sex-specific associations between autonomic nervous system (ANS) activity and TMD pain-related diagnoses in a population-based study.
Methods: The study was part of the Northern Finland Birth Cohort 1966. Of the cohort members, 1964 (62.3% of those invited to oral health examination) were clinically examined as part of the 46-year follow-up. ANS activity was assessed by means of heart rate variability (HRV) and baroreflex sensitivity (BRS). A total of 5 TMD diagnoses were based on the modified protocol of DC/TMD (Diagnostic Criteria for TMD). Of those, pain-related diagnoses, i.e., myalgia and arthralgia, were used. In logistic regression analyses stratified by sex assigned at birth, potential confounders, i.e., education, body mass index, and number of body pain sites, were considered.
Results: Those with TMD myalgia (n = 97) or arthralgia diagnoses (n = 102) had lower values of BRS while standing when adjusted for covariates among females (for myalgia OR 0.847, 95% Cl 0.744-0.964, p = 0.012) and for arthralgia (OR 0.871, 95% Cl 0.775-0.970, p = 0.021).
Conclusion: The results suggest that lowered baroreflex sensitivity, indicating increased sympathetic tone, associates with TMD pain, at least to some extent, in females. These findings refer to the association of stress response with TMD.